A Web-Based Programme for Person-Centred Learning and Support Designed for Preschool Children with Long-Term Illness: A Pilot Study of a New Intervention - Anna-Lena Hellström; Agneta Simeonsdotter Svensson; Ingrid Pramling Samuelsson; Margaretha Jenholt Nolbris (Hindawi Limited, 2012)
For children living with long-term illness, school age is a risk period with regard to psychosocial ill health and poor compliance with treatment. There is a need for methods to promote health, well-being, and self-esteem. This study describes a new concept for supporting children, person-centred web-based learning and support, which has been tested in 12 preschool children and incorporates learning about feelings, relationships, and the right to integrity. SKYPE was used for conversations between the child and the web teacher. Methods. The programme was developed and tested in two steps. The conversations were tape-recorded and analysed using phenomenography. The questions addressed concerned the quality of the intervention process: accessibility of intervention, learning content and support, and identification of measurable items and patterns. Findings. The children found it interesting to communicate with their web teacher using SKYPE. The story about Max and Sara served as a good basis for discussion, and development was found in the learning process. The children were able to talk about relations and feelings and developed an understanding for use in new situations in their daily lives. Items and patterns that are useful for research and documentation were identified, for example, well-being, resources, needs, and wishes.